2016
DOI: 10.1111/jphp.12560
|View full text |Cite
|
Sign up to set email alerts
|

Oral pharmacokinetics and in-vitro metabolism of metyrapone in male rats

Abstract: In this study, we elucidated the plasma pharmacokinetics of MP and its metabolites in male rats after an oral administration. MPOL is most likely to be produced by 11β-HSD1 in the male rats and humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…MP which contains a ketone group is reduced to a secondary alcohol metabolite, metyrapol (MPOL) (Figure 1). Our recent study [11] demonstrated that, after a single oral administration of MP to male Wistar rats, MPOL was the major metabolite and its concentration was maintained at levels higher than these for MP in plasma. The major site involved in the reduction to MPOL in the rats is the liver, and the high MP reducing activity is presented in the liver microsomal fraction [11].…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…MP which contains a ketone group is reduced to a secondary alcohol metabolite, metyrapol (MPOL) (Figure 1). Our recent study [11] demonstrated that, after a single oral administration of MP to male Wistar rats, MPOL was the major metabolite and its concentration was maintained at levels higher than these for MP in plasma. The major site involved in the reduction to MPOL in the rats is the liver, and the high MP reducing activity is presented in the liver microsomal fraction [11].…”
Section: Introductionmentioning
confidence: 93%
“…Our recent study [11] demonstrated that, after a single oral administration of MP to male Wistar rats, MPOL was the major metabolite and its concentration was maintained at levels higher than these for MP in plasma. The major site involved in the reduction to MPOL in the rats is the liver, and the high MP reducing activity is presented in the liver microsomal fraction [11]. Additionally, we previously reported that the rat liver MP-reducing enzyme is present in not only the microsomal fraction but also the mitochondrial fraction [11].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations